INTELLIGENT CUSTOMER SERVICE PLATFORM (ICSP) USING AI ALGORITHMS FOR AUTOMATED SUPPORT (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Plant diseases have major implications on agricultural productivity and food security worldwide. It is even more important for plant disease detection methods to be early and highly specific with respect to effective crop management and yield improvement. Machine learning has evolved into this promising tool to automate identification of plant diseases with pattern recognition techniques based on leaf images and related data.In this framework, classification algorithms like CNNs are trained on huge datasets of plant images to detect visual symptoms of a large number of diseases with high accuracy. The machine-learning-based approach distinguishes between healthy and infected plants and classifies different disease types, allowing timely intervention and limiting dependency on manual inspection. It goes without saying that such systems enjoy more use in actual field conditions if integrated into mobile applications and drones.This study centers around this area of using ML in plant disease detection with emphasis on accuracy, datasets, and real-world implementation challenges. These are poised to act as smart plant health monitoring systems for sustainable agriculture.